Intermediate-term follow-up results of pulmonary balloon valvuloplasty in children - Akçurin, Gayaz; Kahramanyol, Öz; Atakan, Canan (The Turkish Journal of Pediatrics, 2000)
Twenty-two patients (10 boys, 12 girls) with pulmonary valve stenosis whose mean age was 6.7 ± 4.1 years (range 1 to 14 years) at time of the procedure underwent balloon dilatation angioplasty. All patients had isolated pulmonary valve stenosis with no associated cardiac anomalies, and their pulmonary valvular gradients were greater than 50 mmHg. Diagnostic catheterization and balloon valvuloplasty were performed during the same procedure. The mean peak systolic pressure gradient before balloon dilation of 95.8 ± 29.5 mmHg (54-163 mmHg) was reduced to 30.2 ± 15.8 mmHg (7-64 mmHg) after balloon dilation ( p < 0.001 ). A linear relation was found between the predilation pressure gradient and the pressure gradient drop ( r = 0.86 ; SE: 28.94) ( y = 0.89x - 12.11 ). Following a successful valvuloplasty, the mean peak systolic pressure in the right ventricle decreased from 119.0 ± 30.4 mmHg (71-184 mmHg) to 55.2 ± 16.9 mmHg (29-97 mmHg) ( p < 0.001 ). Continuous wave Doppler was used for follow-up. Pressure gradients were estimated in 14 patients between one and 29 months after the dilation 120 ± 7.1 months). The mean follow-up gradient was 19.0 ± 6.0 mmHg (11-32 mmHg). No important complication was noted in the immediate course or throughout the follow-up period, but four patients (28.6%) had minimal pulmonary insufficiency. In conclusion, these data confirm that balloon dilation in valvular pulmonary stenosis is safe and effective, and suggest that stenosis does not recur.
Keywords: congenital heart disease (CHD); pulmonary valvular stenosis; balloon angioplasty